Trends and risk factors of hepatitis A in Catalonia after the introduction of a hepatitis A+B vaccination programme. Issue 9 (26th April 2018) - Godoy, P.; Carmona, G.; Manzanares, S.; Jane, M.; Borràs, E.; Camps, N.; Álvarez, J.; Barrabeig, I.; Sala, M.‐R.; Rius, C.; Minguell, S.; Carol, M.; et al.
Summary: At the end of 1998, universal hepatitis A+B vaccination of 12 year olds was introduced in Catalonia. The aim was to examine trends in hepatitis A during 2005‐2015 and assess risk factors by age group. We carried out an observational epidemiological study of the incidence and risk factors of hepatitis A reported to the surveillance system. Information on exposure was recorded for each case for the 2‐6 weeks before symptom onset. Spearman's coefficient was used to evaluate the trends of rates. The chi‐square test was used to compare categorical. We studied 2621 hepatitis A cases; the age mean was 26.6 years (SD=18.2), and >50% of cases were in the 20‐49 years age group. The incidence decreased from 3.28/100 000 in 2005 to 1.50/100 000 in 2015. The rate for women decreased over time ( P  = .008), but the reduction was not significant in men ( P  = .234). Men consistently had higher rates than women with the biggest difference being in the 20‐34 years age group (rate 8.8 vs 2.8). The greatest risk factor was travel to an endemic country (42.1%) in the 0‐19 years age group and male‐to‐male sexual contact (18.6%) in the 20‐49 years age group. The case fatality rate in adults aged >49 years was 0.4%. In conclusion, the vaccination programme of preadolescents resulted in a reduction in hepatitis A cases. However, a significant amount of cases still appear in immigrants and men who have sex with men. Hepatitis A in adults is an emerging health problem that will require new strategies.